Marriage Services During the Covid-19 Pandemic; Friedman’s Legal System Study Against the Mandatory Rule for Antigen Swab Test - Ahmad Arif Masdar Hilmy; Ahmat Trisno (Fakultas Syariah IAIN Madura, 2023)
Antigen swab test is new to the people of Tempursari District during the COVID-19 pandemic. Circular of the Director-General of Islamic Community Guidance No: P-001/DJ.III/Hk.007/07/2021 is the basis for the mandatory antigen swab regulation for the two prospective brides, a guardian, and two witnesses, which is carried out 1x24 hours before the marriage contract. The Puskesmas is the only place that can be used for an antigen swab test in Tempursari District, while to get the test in another place, you have to travel quite a long time and distance, considering that Tempursari is located at the end of Lumajang Regency. The purpose of this study was to determine the implementation of the mandatory antigen swab regulation at KUA Tempursari, as well as a review of Lawrence M. Friedman's legal system theory on the implementation of the regulation. This field research uses a qualitative descriptive method. Data mining is done by document study, observation, and in-depth interviews. This study resulted in several conclusions: (1) the mandatory rules for antigen swab can be implemented properly by KUA Tempursari employees, as evidenced by the existence of socialization and coordination with various parties, such as P3N and Puskesmas employees, (2) based on Friedman's legal system theory, the implementation of mandatory rules The antigen swab at the KUA Tempursari has covered three aspects, namely the legal structure, legal substance, and legal culture, it can be judged to have been effectively implemented at the KUA Tempursari.